FROM THE RESEARCH OF LOCAL AND FOREIGN SCHOLARS ON ETHNO-POLITICAL PROCESSES ALONG THE LOWER AMU DARY - R.H. Sherniyazov (Western European Studies, 2025)
In this article, a number of local and Russian historians, tourists, ethnopolitical and ethnocultural processes that took place among the inhabitants of the Lower Amudarya basin, especially the parallel ethnonyms between the Turkmen-Uzbek, Turkmen-Karakalpak, Turkmen-Kazakh clans, written sources, archival materials, statistics It is said that it was conducted and studied based on data and ethnographic research.
Keywords: Lower Amudarya; Zarafshan; Armeni Vamberi